2014
DOI: 10.1136/sextrans-2013-051384
|View full text |Cite
|
Sign up to set email alerts
|

Cross-sectional study of genital carcinogenic HPV infections in Paramaribo, Suriname: prevalence and determinants in an ethnically diverse population of women in a pre-vaccination era

Abstract: Carcinogenic HPV is highly prevalent among women in Suriname, and not equally distributed among ethnic groups. These data provide a baseline to assess possible shifts in the prevalence of HPV genotypes following vaccination.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

3
10
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(13 citation statements)
references
References 28 publications
3
10
0
Order By: Relevance
“…Cervical HPV prevalence in this study is similar to that reported in high-risk populations ( 20 , 21 ) and higher than in other reports that used the same detection method, in Latin America (37 to 51%) ( 20 , 22 ), Europe (<20%) ( 23 ), and Japan (<20%) ( 24 ). This disparity in prevalence may be due to the high prevalence of anemia and intestinal helminthes, which may reduce HPV clearance ( 25 ), degree of isolation from the global HPV pool, etc., while for industrialized countries, vaccination is significantly reducing HPV infection ( 26 , 27 ).…”
Section: Discussionsupporting
confidence: 86%
“…Cervical HPV prevalence in this study is similar to that reported in high-risk populations ( 20 , 21 ) and higher than in other reports that used the same detection method, in Latin America (37 to 51%) ( 20 , 22 ), Europe (<20%) ( 23 ), and Japan (<20%) ( 24 ). This disparity in prevalence may be due to the high prevalence of anemia and intestinal helminthes, which may reduce HPV clearance ( 25 ), degree of isolation from the global HPV pool, etc., while for industrialized countries, vaccination is significantly reducing HPV infection ( 26 , 27 ).…”
Section: Discussionsupporting
confidence: 86%
“…Other methods maybe be less sensitive, consistent with the lower prevalences reported for Latin America and Caribbean region in high-grade squamous intraepithelial lesions (41–67%) ( Parkin et al, 2008 ). High HPV prevalence ranging from 30 to 50% have been reported for other high-risk Latin American countries, using the same genotyping method SPF 25 /LiPA 10 , including anal specimens in Costa Rica ( Castro et al, 2012 ), and vaginal specimens in Surinam ( Geraets et al, 2014 ), as well as for Nigeria ( Adebamowo et al, 2017 ), Turkey ( Barut et al, 2018 ), and Italy ( Carozzi et al, 2018 ). The very high prevalence found in our study may reflect the high-risk patients from the San Juan Municipality, known to have rising cervical cancer diagnoses ( Registro Central De Cáncer De Puerto Rico, 2017 ).…”
Section: Discussionmentioning
confidence: 85%
“…The science of cytokines is still being worked out, and far from an intervention. But its potential importance in STI control is borne out when we consider the extraordinarily high burdens of STI still borne by many populations in the developing world, which are also reported this month by Abdool-Karim et al ,10 Lurie et al 11 from South Africa, and Geraets12 from Suriname.…”
mentioning
confidence: 81%